BAFF Index and CXCL13 levels in the cerebrospinal fluid associate respectively with intrathecal IgG synthesis and cortical atrophy in multiple sclerosis at clinical onset. Issue 1 (December 2017) - Puthenparampil, M.; Federle, L.; Miante, S.; Zito, A.; Toffanin, E.; Ruggero, S.; Ermani, M.; Pravato, S.; Poggiali, D.; Perini, P.; Rinaldi, F.; Gallo, P.
Abstract Background B lymphocytes are thought to play a relevant role in multiple sclerosis (MS) pathology. The in vivo analysis of intrathecally produced B cell-related cytokines may help to clarify the mechanisms of B cell recruitment and immunoglobulin production within the central nervous system (CNS) in MS. Methods Paired cerebrospinal fluid (CSF) and serum specimens from 40 clinically isolated syndrome suggestive of MS or early-onset relapsing-remitting MS patients (CIS/eRRMS) and 17 healthy controls (HC) were analyzed for the intrathecal synthesis of IgG (quantitative formulae and IgG oligoclonal bands, IgGOB), CXCL13, BAFF, and IL-21. 3D-FLAIR, 3D-DIR, and 3D-T1 MRI sequences were applied to evaluate white matter (WM) and gray matter (GM) lesions and global cortical thickness (gCTh). Results Compared to HC, CIS/eRRMS having IgGOB (IgGOB+, 26 patients) had higher intrathecal IgG indexes (p  < 0.01), lower values of BAFF Index (11.9 ± 6.1 vs 17.5 ± 5.2, p  < 0.01), and higher CSF CXCL13 levels (27.7 ± 33.5 vs 0.9 ± 1.5, p  < 0.005). In these patients, BAFF Index but not CSF CXCL13 levels inversely correlated with the intrathecal IgG synthesis (r  > 0.5 andp  < 0.05 for all correlations). CSF leukocyte counts were significantly higher in IgGOB+ compared to IgGOB− (p  < 0.05) and HC (p  < 0.01), and correlated to CSF CXCL13 concentrations (r 0.77, p  < 0.001). The gCTh was significantly lower in patients with higher CSF CXCL13 levels (2.41 ± 0.1 vs 2.49 ± 0.1 mm, p  < 0.05), while no difference in MRI parameters of WM and GM pathology was observed between IgGOB+ and IgGOB−. Conclusions The intrathecal IgG synthesis inversely correlated with BAFF Index and showed no correlation with CSF CXCL13. These findings seem to indicate that intrathecally synthesized IgG are produced by long-term PCs that have entered the CNS from the peripheral blood, rather than produced by PCs developed in the meningeal follicle-like structures (FLS). In this study, CXCL13 identifies a subgroup of MS patients characterized by higher leukocyte counts in the CSF and early evidence of cortical thinning, further suggesting a role for this chemokine as a possible marker of disease severity.